Governance Challenges in Bridging Theory and Practice: Indonesian Foreign Policy - Siregar, Rifqi Mulya Nauli; Bainus, Arry; Darmawan, Wawan Budi (Jurnal Pemerintahan dan Politik Lokal, 2025)
This paper examines challenges that Indonesia potentially faces in bridging theory-practice gaps in foreign policy formulation. Using qualitative library research methodology with document analysis based on George's (1993) theoretical framework, the research identifies six key potential challenges: cultural and epistemological divergences between academics and policymakers, language barriers, difficulties in accurately analyzing external actors, limitations of abstract theoretical models, and structural-institutional constraints within Indonesia's knowledge ecosystem. The findings suggest these challenges potentially result in less coherent and more reactive foreign policy decisions. This research contributes to the limited discourse on theory-practice gaps in Indonesian foreign policy studies, offering insights for strengthening evidence-based policy formulation in navigating complex regional dynamics. The paper argues that developing platforms for knowledge exchange, reforming institutional incentives, and strengthening analytical capacity within Indonesia's foreign policy bureaucracy are essential steps forward. Despite recent positive developments in institutional reform, fundamental challenges in epistemic culture and knowledge integration mechanisms still require special attention to enhance Indonesia's strategic positioning in an increasingly complex geopolitical environment.